Metacognitive Therapy for Work-Related Stress: A Feasibility Study - De Dominicis, Stefano; Troen, Maiken Lykke; Callesen, Pia (Frontiers in Psychiatry, 2021)
About 25% of EU workers experience work-related stress for all or most of their working time, showing that work-related stress is a major cause of health problems for the EU population. This situation has been worsened even more by the COVID-19 restrictions embraced by employers worldwide. However, a timely and sustainable intervention protocol for treating such issues has not been developed yet. Thus, the present research shows a first effective attempt based on Metacognitive therapy (MCT) to solve this issue. MCT was practiced on four individuals suffering from chronic work-related stress. Primary outcome variables were general mental health, perceived stress, and blood pressure. Participants were assessed at multiple baselines before the start of therapy and then attended a 3- and 6-months follow-up after treatment termination. Results showed significant improvements in general mental health, perceived stress, and blood pressure in each client. Secondary outcome variables improved too —maladaptive coping strategies, avoidance behaviors, and depression symptoms—corroborating the main findings. At 3- and 6-month follow-up, results were maintained. The findings suggest that MCT might be a promising and sustainable intervention for work-related stress, although a metacognitive model for stress and large-scale RCTs need to be developed and carried out to further explore the effect of MCT on stress. Our results represent one of the first attempts to treat work-related stress via Metacognitive Therapy and support the feasibility of the treatment, both in terms of its efficacy and sustainability, in a historical moment in which work-related stress is increased worldwide because of the COVID-19 pandemic. Within such a realm, our feasibility study should be followed by larger and controlled studies that, if successful, would provide various stakeholders—including organizational and institutional decision-makers—with a solid, timely and cost-effective method to help the workforce coping with work-related stress.